Pencegahan Konstipasi pada Ibu Nifas dengan Early Exercise - Laili, Uliyatul; Nisa, Fauziyatun (Jurnal Bidan Cerdas, 2019)
In Indonesia, many postpartum mothers experience constipation. Some of the contributing factors include less of movement after childbirth (early mobilization), poor nutritional intake, low fluid intake, narcotic-containing pain relievers leaving the intestines and periodic spasms of the small intestine. The purpose of this study was to find out the effect of giving care in the form of early exercise or early physical exercise in an effort to prevent constipation during the puerperium. The research method used was quasi-experiment; with the population were postpartum mothers on the first day up to the fifth day. Data collections were done by questionnaire and observations then tested by Mann Whitney test. The result of this study is that there was no effect between giving care in the form of early exercise to the incidence of constipation in postpartum mothers, a significance value of 0.678> 0.005. The conclusion of this study is that there were many other factors that influence the incidence of constipation in addition to activity factors, namely anxiety, suture injuries, current and past labor history and nutritional intake.